Reflection of the Diaspora in the Fantasy of a Totalitarian Society - Kanchura, Yevheniia (Literatūra, 2025)
This paper presents a comparative analysis of fantasy works from two distinct periods: the late Soviet (Vladislav Krapivin’s A Dovecote on a Yellow Meadow, 1983–1985) and the post-Soviet period (Max Frei’s The Stranger, 1996, and The Master of Winds and Sunsets, 2014). The portal-quest fantasy plot, which involves a character’s transition from the mundane reality to a fantasy world, is marked in both works by reflective elements concerning the protagonist’s potential interactions with their fellow compatriots encountered in the new reality. The study identifies three models of such interaction. In the fantasy of the totalitarian era (V. Krapivin), there is a nostalgic idealization of homeland and immediate acceptance of the fellow compatriot, resulting in the formation of a cohesive and effective diaspora supporting the fight to save the world from the totalitarian ideological system. In contrast, Max Frei’s post-Soviet fantasy initially portrays a sharp rejection of fellow compatriots, perceiving them as a threat to the other world (The Stranger). This perspective later evolves into a third model: acceptance and support of individuals who are kindred in spirit, regardless of their origin (The Master …). The study concludes that these narratives reflect the evolving perception of immigration and diaspora, from within a totalitarian society (V. Krapivin) to the perspective of an individual who has transcended its boundaries (Max Frei).